2003
DOI: 10.2114/jpa.22.143
|View full text |Cite
|
Sign up to set email alerts
|

Change in Double Product during Stepwise Incremental Exercise

Abstract: The purpose of this study was to observe the change in double product with increases in the intensity of bicycle exercise. Eleven young male adults participated in this study. The subjects performed graded bicycling exercise increasing 20 watts every 2 min from 0 watts until the heart rate (HR) reached 170 beats · min Ϫ1 . During exercise systolic blood pressure (SBP) and HR were continuously measured. Initially SBP gradually increased with the increase in workload, but when the intensity of exercise became ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Participants performed a GXT before and after the HIIT program (described below), and, on both occasions, anthropometric and resting heart rate (HR rest ), systolic (SBP) and diastolic (DBP) blood pressure were measured. Rate pressure product (RPP) was calculated as the product of heart rate and SBP (Kim, Choi, Takahashi, Kurokawa, & Yamasaki, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Participants performed a GXT before and after the HIIT program (described below), and, on both occasions, anthropometric and resting heart rate (HR rest ), systolic (SBP) and diastolic (DBP) blood pressure were measured. Rate pressure product (RPP) was calculated as the product of heart rate and SBP (Kim, Choi, Takahashi, Kurokawa, & Yamasaki, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The primary end‐point was to evaluate the response of sCgA and sAA throughout exercise and recovery. DP (systolic blood pressure × heart rate) 24 and the RPE‐session, calculated as RPE x duration of the exercise in minutes, were used as indices of intensity of cardiovascular and psychological responses to the physical exercise. Normality of continuous data distribution was explored by Kolmogorov–Smirnov test.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to investigate (i) whether physical exercise might influence significantly sCgA secretion; (ii) the possible correlation between sCgA and sAA secretion with physiological and psychological parameters of stress 1–3 . In particular, integrating heart rate and blood pressure variables, the double product (DP) was chosen as an objective index of the physiological changes evoked by high‐intensity physical stress through SAM activation, 24 whereas the product of the subjective rating of perceived exertion (RPE) 25 and the exercise duration (min) was considered an index of exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The DP has been a useful index in cardiac rehabilitation settings to identify specific workloads at which signs and symptoms of ischemia occur, and improvements in functional capacity relative to the onset of symptomatic ischemia (Arya et al 2005;Durstine and Tanaka and colleagues were the first to identify that the DP increases more rapidly above the LT than below it, and were the first to identify a breakpoint in the double product (DPBP) with incremental exercise in healthy subjects Tanaka and Shindo 1992). Several other studies have further examined the occurrence of the DPBP in healthy subjects as well as those with coronary artery disease (CAD), (Brubaker et al 1997;Kim et al 2003;Omiya et al 2004;Riley et al 1997), and have found that the DPBP occurs at similar exercise intensities to that of the lactate threshold (LT) and ventilatory threshold (VT). They conclude that the DPBP may be a useful non-invasive, and easier to obtain marker of the LT and VT in a wide range of individuals.…”
Section: Introductionmentioning
confidence: 99%